2002
DOI: 10.1597/1545-1569_2002_039_0397_soiicp_2.0.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Speech Outcomes in Isolated Cleft Palate: Impact of Cleft Extent and Additional Malformations

Abstract: Objective The purpose of the study was to study the speech outcome in a series of 5-year-old children born with an isolated cleft palate and compare the speech with that of noncleft children and to study the impact of cleft extent and additional malformation on the speech outcome. Design A cross-sectional retrospective study. Setting A university hospital serving a population of 1.5 million inhabitants. Subjects Fifty-one patients with an isolated cleft palate; 22 of these had additional malformations. Thirtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
3
25
1
3
Order By: Relevance
“…A comparable high occurrence of hypernasality was also found in the CPS group (20%). The result in the CPH group was similar to what was found by Persson et al (2002), who evaluated speech after a two-stage protocol. However, 6% in the CPS group were rated as having moderate hypernasality.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…A comparable high occurrence of hypernasality was also found in the CPS group (20%). The result in the CPH group was similar to what was found by Persson et al (2002), who evaluated speech after a two-stage protocol. However, 6% in the CPS group were rated as having moderate hypernasality.…”
Section: Resultssupporting
confidence: 86%
“…The corresponding figure at around 10 years of age was around 80% (Lohmander, 2011). In a national prospective study in the United Kingdom, Sell et al (2001) It has been suggested that the cleft extent has an impact on speech outcome in children born with CPO -that is, the larger the extent of the cleft, the higher the impact on both velopharyngeal function (Brunnegård & Lohmander, 2007;Nyberg et al, 2010;Bicknell et al, 2002) and articulation (Persson et al, 2002). The influence of the cleft extent on articulation reported in earlier studies (Jakobsson et al, 1990;Lohmander-Agerskov et al, 1993), was confirmed in the study by Persson et al (2006), who showed a higher prevalence of retracted oral articulation in children with CPH than in children with CPS.…”
Section: Cleft Palate and Speech Outcomesmentioning
confidence: 99%
“…Diverse factors are attributed to suboptimal repair such as age at the time of the surgery, skills and experience of the surgeon, type and extension of the cleft, fibrosis, damage of the motor and proprioceptive innervation, and abnormal fiber type distribution. 7,[9][10][11][12] This review will highlight the myogenesis and characteristics of the soft palate muscles in the noncleft and cleft palate, and the process of muscle regeneration. We postulate that muscle healing and function after soft palate repair can be improved by adjuvant strategies from the field of regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…LEE, 2003;HENNINGSSON et al, 2008). Já a emissão de ar nasal é definida como um escape de ar (audível ou não) através da válvula velofaríngea (JOHNS;ROHRICH;AWADA, 2003;BRIGGS;LEE, 2003;TRINDADE et al, 2005;HENNINGSSON et al, 2008;KUMMER, 2008 -CARDAMONE, 1989;SEAGLE et al, 2002;CABLE et al, 2004;MALICK;CANADY, 2007;KUMMER, 2008;TUNA et al, 2010;NABI et al, 2011;KUMMER et al, 2012;SAMAN;TATUM III, 2012 DOTEVAL et al, 2002;PERSSON et al, 2002;SELL et al, 2002;SOMMERLAD et al, 2002;VAN LIERDE et al, 2002;BRIGGS;LEE, 2003;MEHENDALE et al, 2004;VAN LIERDE et al, 2004;LIEDMAN-BOSHKO et al, 2005;PAAL et al, 2005;TRINDADE et al, 2005;JOHN et al, 2006;PERSSON;LOHMANDER;ELANDER, 2006;BRUNNEGARD;LOHMANDER, 2007;HOLLAND et al, 2007;VAN LIERDE et al, 2007;HENNINGSSON et al, 2008;KHO...…”
Section: àS Demais Colegas De Trabalho Toda Equipe Competente Do Cenunclassified
“…Whitehill et al, (2002) sugerem que a nasalidade é uma sensação perceptiva protética e que, portanto, não poderiam ser classificadas por meio de escalas de intervalos iguais, uma vez que este tipo de escala demanda dos ouvintes partilhar as sensações em categorias discretas. Entretanto, este tipo de escala é muito comum nos estudos que investigam fala e ressonância (DALSTON et al, 1991;HARDIN et al, 1992;WATTERSON et al, 1998 , 2000;DOTEVAL et al, 2002;PERSSON et al, 2002;SELL et al, 2002;SOMMERLAD et al, 2002;VAN LIERDE et al, 2002;BRIGGS;LEE, 2003;MEHENDALE et al, 2004;VAN LIERDE et al, 2004;LIEDMAN-BOSHKO et al, 2005;PAAL et al, 2005;TRINDADE et al, 2005;JOHN et al, 2006;PERSSON;LOHMANDER;ELANDER, 2006;BRUNNEGARD;LOHMANDER, 2007;HOLLAND et al, 2007;VAN LIERDE et al, 2007;HAVSTAM et al, 2008;HENNINGSSON et al, 2008;KHOSLA;MABRY;CASTIGLIONE, 2008;LOHMANDER;PERSSON, 2008;SWEENEY;SELL, 2008;LOHMANDER et al, 2009;RULLO et al, 2009;BAYLIS;MUNSON;MOLLER, 2010;…”
Section: Concordância Intragrupo De Juízasunclassified